Pirates of the purple dawn - Abbott, Tony, 1952-; Fitzgerald, Royce; Jessell, Tim. (New York : Scholastic Inc., 2007)
Everything in Droon is changing. Lord Sparr has disappeared. Ko and Gethwing have fled to the Dark Lands. And an old villain is back -- Ving, leader of the Hawk Bandits! This time, he has his twin sister in tow, along with her band of wicked pirates. Arrrg! They're snatching magical stones from all over Droon, and using them to build an enchanted passageway that will transport nasty dragons from the past into the present. Can Eric and his friends put a stop to the pirates? Or will they be lost at sea?
G4
Keywords: Droon (Imaginary place) -- Juvenile fiction; Wizards -- Juvenile fiction; Magic -- Fiction; Droon (Imaginary place) -- Fiction; Wizards -- Fiction; Children's stories; Fantasy fiction